2007
DOI: 10.1016/j.heares.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of auditory cortex in the formation of auditory streams

Abstract: Auditory streaming refers to the perceptual parsing of acoustic sequences into "streams", which makes it possible for a listener to follow the sounds from a given source amidst other sounds. Streaming is currently regarded as an important function of the auditory system in both humans and animals, crucial for survival in environments that typically contain multiple sound sources. This article reviews recent findings concerning the possible neural mechanisms behind this perceptual phenomenon at the level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
125
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(138 citation statements)
references
References 79 publications
9
125
1
Order By: Relevance
“…Our finding that regions in the PT adjacent to, and touching upon, Heschl's gyrus and sulcus discriminate stimuli on a purely perceptual level goes beyond such a limited featurebound processing role. It is, however, in line with single-cell recording studies in monkeys and cats (Micheyl et al, , 2007Nelken and Bar-Yosef, 2008). For instance, object representations have been suggested to be present even as early as in A1 (Bar-Yosef and Nelken, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…Our finding that regions in the PT adjacent to, and touching upon, Heschl's gyrus and sulcus discriminate stimuli on a purely perceptual level goes beyond such a limited featurebound processing role. It is, however, in line with single-cell recording studies in monkeys and cats (Micheyl et al, , 2007Nelken and Bar-Yosef, 2008). For instance, object representations have been suggested to be present even as early as in A1 (Bar-Yosef and Nelken, 2007).…”
Section: Discussionsupporting
confidence: 75%
“…The present findings indicate a more broadly distributed sensitivity to f 0 that may reflect neuronal sensitivity to the differing temporal properties of tones of different f 0 , rather than a sensitivity to pitch per se. Frequency-selective forward suppression of neural responses in the auditory cortex (or the equivalent in nonmammalian species) has been proposed to play an essential role in auditory streaming (Fishman et al, 2001(Fishman et al, , 2004Kanwal et al, 2003;Klump, 2004, 2005;Micheyl et al, 2005Micheyl et al, , 2007. Specifically, it has been suggested that whether a sequence of pure tones is perceived as a single coherent stream or as two separate streams depends on the degree to which one tone influences the responses to subsequent tones.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological studies cited above are generally consistent with these theoretic models. In particular, the animal studies (reviewed by Micheyl et al, 2007) have specifically demonstrated a relationship between streaming and two-tone interactions within frequency-selective neurons of primary auditory cortex.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has started to attract the interest of both animal behaviorists and neuroscientists (for reviews, see Carlyon 2004; Micheyl et al 2007b;Snyder and Alain 2007;Bee and Micheyl 2008;Fay 2008;Shamma and Micheyl 2010). In this context, it is desirable for experimenters to have at their disposal measures of auditory streaming that do not rely on reports of perceived segregation (such as "one stream" versus "two stream" judgments).…”
Section: Introductionmentioning
confidence: 99%